Analysis of the Effectiveness of Statistical Methods in Improving Educational Performance - Deyanira Elizabeth Paz Rubio; Segundo Ignacio Ponte Valverde; Elsa Noemi Guillén Guillén; Andrea Mercedes Álvarez Rubio; Luis Bautista López; Aracelli Mónica Aguado Lingán (Migration Letters, 2023)
A documentary review was carried out on the production and publication of research papers related to the study of the variables Statistical Methods and Academic Performance. The purpose of the bibliometric analysis proposed in this document was to know the main characteristics of the volume of publications registered in the Scopus database during the period 2017-2022 by Latin American institutions, achieving the identification of 123 publications. The information provided by this platform was organized through graphs and figures, categorizing the information by Year of Publication, Country of Origin, Area of Knowledge and Type of Publication. Once these characteristics have been described, the position of different authors on the proposed topic is referenced through a qualitative analysis. Among the main findings made through this research, it is found that Brazil, with 43 publications, was the Latin American country with the highest scientific production registered in the name of authors affiliated with institutions of that nation. The Area of Knowledge that made the greatest contribution to the construction of bibliographic material related to the study of Academic Performance and Statistical Methods was Medicine with 53 published documents, and the most used Publication Type during the period indicated above were Journal Articles with 91% of the total scientific production.